(untitled) (Mustansiria Dental Journal, 2018)
Color Doppler ultra sound is an ideal imaging tool for initial assessment of intranodular vascularity which may reflect some pathological behaviors of tumors and lymph nodes in patients with cervical lymphadenopathy. The aim of this study was to evaluate the usefulness of Color Doppler ultra sound in differentiating benign from malignant cervical lymph nodes by the assessment of Nodal vascularity. In a prospective study of 24 untreated patient with 65 cervical lymph nodes clinically including enlarged hard and soft palpable and non palpable lymph nodes . All these lymph nodes were evaluated with Color Doppler ultra sound as a pre-surgical diagnostic tool, the findings were compared with histo-pathalogical results. Fine needle Aspiration cytology was used for 15 palpable enlarged cervical lymph nodes, most of these lymph nodes 12 lymph nodes were associated with reactive lymph nodes and not operated on, just follow up with antibiotic treatment and performed only 3 lymph nodes were associated with malignant lymph nodes which removed surgically and assessed histopathologically. Upon Color Doppler ultra sound examination pre-operatively of 65 cervical lymph nodes were found 20 lymph nodes as a reactive lymph nodes and 45 as malignant lymph nodes. After neck dissection, all lymph nodes histo-pathologically examined which showed 22 benign lymph nodes and 43 lymph nodes containing metastases. Nodal vasculature were classified into: · Hilar · Capsular · Hilar with capsular vascularity Results: most of the malignant nodes showed the presence of capsular vascularity and capsular with hilar vascularity, 37.2% and 48.8% respectively, where as the majority of the reactive nodes showed hilar vascularity 77.3% and the different was highly significant P<0.01 when chi-square was used. Conclusion: the distribution of intra nodal vascularity appears to be useful in differentiating benign from malignant cervical lymph nodes by means Color Doppler ultra sound which consider as a routine pre-surgical tool to provide the surgeons with a valuable information that aids them to modify their surgical management